Implementation of Keputrian Activities in Female Students’ Spiritual Development in Public Schools - Lu’luaturroisah Lu’luaturroisah; Nur Rohmah Hayati (Darul Yasin Al Sys, 2026)
The spiritual development of female students in public schools requires structured and contextually relevant programs that address both religious understanding and everyday behavioural formation. This study aimed to examine how keputrian activities are implemented to support the spiritual development of female students at SMA Negeri 6 Purworejo. A qualitative approach with a case study design was employed to explore the phenomenon in its natural setting. The study involved the principal, a female Islamic education teacher serving as the keputrian mentor, and two female students from different grade levels selected purposively. Data were collected through in-depth interviews, direct observation, and document analysis, with the researcher functioning as the primary instrument. The analysis followed an interactive process of data organization, interpretation, and conclusion development. The findings indicate that the program is implemented consistently with institutional support while remaining responsive to students’ needs. The mentoring process emphasizes dialogical interaction, the delivery of contextual material, and the habituation of religious values. The study further found improvements in students’ awareness of religious practices, understanding of women-related issues in Islam, and behavioural control in daily life, although the internalization of spiritual values varied according to individual awareness and the surrounding social environment. This study concludes that keputrian activities can serve as an effective medium for strengthening female students’ spiritual development in public schools when supported by sustained institutional commitment and adaptive mentoring practices.